Idaho - George, Charles; George, Linda (New York : Children's Press, 2000)
Describes the geography, plants, animals, history, economy, religions, culture, sports, arts, and people of Idaho.
Includes bibliographical referenes and index.
Keywords: Idaho -- Juvenile literature